Combating trafficking of Hungarian women to Western Europe: a multi-level analysis of the international law enforcement cooperation - Katona, Noémi (Trends in organized crime, 2020)
Human trafficking is an increasing field of academic research, but the obstacles of investigation and prosecution of traffickers is still under-researched. This article analyses the challenges of prosecution of criminal groups facilitating the prostitution of Hungarian women to Western European countries by focusing on international cooperation of law enforcement agencies. Although the scientific literature mostly focuses on the influence of international agreements on national level policing, based on a multilevel analysis, the current article scrutinizes the organizational and individual dimensions in transnational policing and the implementation of the anti-trafficking measures in practice. Despite the aims of the global prohibition regime, victim-focus approach in human trafficking remains neglected by large in the Hungarian practice. The article is based on structured interviews with members of law enforcement agencies, observation of court trials, legal documents and secondary written sources on the investigation of organized crime in Hungary.